MORE MARKETING MANAGEMENT CASES IN MALAYSIA - Sieh, Mei Ling (Utusan Publications & Distributors Sdn Bhd, 1999)
Republication of Marketing management cases in Malaysia, with the addition of 12 new cases studies.